Imagem e consumo: A comunicação da marca Unilever/Ades nas plataformas digitais - Dos Santos Gonzales, Lucilene [UNESP]; Luvizotto, Caroline Kraus [UNESP] (Universidade Estadual de Londrina, 2015)
Understanding the importance of images for consumption as well as the Internet and Web 2.0 technologies for marketing communication, this article focuses on the potential image as influencing agent in consumer relations. Specifically, demonstrates the case of Unilever and its Ades product, analyzing how the images used on the website and in the Fan Page of the brand influence consumers.
Image and consumption: The communication Unilever/Ades brand on digital platforms
Keywords: Consumption; Image; Internet; Marketing communication